The role of special schools for children with profound and multiple learning difficulties: Is segregation always best? - Simmons, B; Bayliss, P (2007)
The education of young people with profound and multiple learning difficulties continues to raise challenges and controversies. In this article, Ben Simmons, an ESRC funded PhD student and research assistant, and Phil Bayliss, programme director for the masters degree in special education and disability, both based in the School of Education and Lifelong Learning at the University of Exeter, describe their research into provision for pupils with profound and multiple learning difficulties in a special school in the south west of England. Their work, based in an interpretivist, qualitative approach, set out to illuminate issues relating to the inclusion of pupils with profound and multiple learning difficulties. The findings presented here suggest that the school, in spite of its strong reputation, struggled significantly to provide appropriate learning experiences for pupils with profound and multiple learning difficulties. Ben Simmons and Phil Bayliss discuss the need for improved staff development opportunities focused on enhancing current levels of knowledge and skills. They conclude by calling for a reappraisal of the established view that special schools necessarily provide the best learning environment for pupils with profound and multiple learning difficulties. © Nasen 2007.